Recent discovery of plant-derived anti-diabetic natural products - Hung, Hsin-Yi; Qian, Keduo; Morris-Natschke, Susan L; Hsu, Chau-Shin; Lee, Kuo-Hsiung (Natural product reports, 2012)
Covering: 2005 to 2010 This review covers recent discoveries of anti-diabetic compounds. Diabetes mellitus (DM) is a complex disease affecting patients' daily life and elevating patients' risk of developing other diseases. There are several forms of diabetes, including type-1 diabetes (insulin-dependent), type-2 diabetes (noninsulin-dependent), and gestational diabetes. Type-2 diabetes is the most common form and the patient population with type-2 DM rises every year. Current treatments meet some but not all patients' needs. Therefore, new anti-diabetic drugs are in great demand. Traditional herbal medicine provides a rich source for new drug discovery. In this review, recent discoveries of anti-diabetic compounds have been summarized according to their chemical structures and mechanisms of action. Anti-diabetic plant extracts, many of which have been used and marketed as dietary supplements, were also included and discussed, and are classified according to the positive control used in the anti-diabetic animal studies. New anti-diabetic natural products found in the recent patent literature are also summarized. Recent discoveries of plant-derived anti-diabetic natural products, plant extracts, and patent literature are reviewed. As examples, two acylated kaempferol compounds ( 2 , 3 ) exhibited significant -glucosidase inhibition, and two quassinoids ( 4 , 5 ) showed comparable blood sugar lowering effects in vivo with glibenclamide.